Simultaneous Design and Control of a Semibatch Styrene Polymerization Reactor - Asteasuain, Mariano (2004)
It has been established that the security, flexibility, and dynamic controllability of a process are inherent properties of its design, which also affects process economics. In this context, we employed a previously developed mixed-integer dynamic optimization (MIDO) approach to perform the simultaneous design and control of styrene polymerization reactors. Industrial- and laboratory-size semibatch jacketed reactors were considered. The gPROMS/gOPT package was successfully used to solve the mixed-integer dynamic optimizations. In each case, the geometry, initiator mixture composition, and control system were optimally determined in a single optimization run. We analyzed the effect of using different coolants with and without heat supply on the laboratory-scale reactor design. We also studied the effect of scale-up in the integrated process and control design. Design coincidences and differences were analyzed.